2023
DOI: 10.1002/hsr2.1070
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and the risk of NICU admissions in Nandom Municipality of Ghana: A cross‐sectional retrospective study

Abstract: Background Neonatal intensive care units (NICU) are specialized units that provide medical attention to neonates, and thus have become a vital aspect in the provision of critical care to infants who are faced with special challenges following birth. Aim To determine antepartum and intrapartum factors that predispose to NICU admissions in the Nandom Municipal of the Upper West Region of Ghana. Method This was a cross‐sectional retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…This result is in line with a similar study conducted in the Northern part of Ghana [ 33 ]. Moreover, previous studies have consistently reported a significant association between caesarean delivery and an increased likelihood of NICU admission among neonates [ 34 36 ]. Indeed, babies referred to the neonatal intensive care unit (NICU) are more likely to have been delivered by caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with a similar study conducted in the Northern part of Ghana [ 33 ]. Moreover, previous studies have consistently reported a significant association between caesarean delivery and an increased likelihood of NICU admission among neonates [ 34 36 ]. Indeed, babies referred to the neonatal intensive care unit (NICU) are more likely to have been delivered by caesarean section.…”
Section: Discussionmentioning
confidence: 99%